Les femmes et les plantes : accès négocié à la botanique savante et résistance des savoirs vernaculaires (France, xviiie siècle) - Émilie-Anne Pépy (Genre & Histoire)
This paper aims to show how women negotiated opportunities for access to botanical knowledge and the therapeutic use of plants, despite their exclusion from universities, academies and medical corporations. During the eighteenth century, the male monopoly on these areas of expertise was consolidated, and women’s autonomy was denied. However, as botany was becoming a fashionable and socially accepted activity, a few learned women from the social elites managed to engage in mainstream scientific practice. Until the middle of the nineteenth century, however, it was easier for female herbalists and care-givers to continue using medicinal plants, because they were still important actors in the medical marketplace.